Implementasi Kegiatan Ekstrakurikuler Tahfizh Qur’an Di MAN 2 Agam - Rizki Rahmad; Januar Januar (STIKes Ibnu Sina Ajibarang, 2023)
This research is motivated by the reality at MAN 2 Agam which shows that students' memorization is not maximal in achieving it according to the target given, there are also students who like to disturb their friends in the process of reciting the Qur'an, less effective place and time for extracurricular tahfizh implementation Qur'an, the lack of strict rules related to the tahfiz program at MAN 2 Agam, and the teacher's lack of optimality in carrying out extracurricular tahfizh Qur'an. The method used in this research is a qualitative research method. The key informants in this study were tahfizh mentor teachers at MAN 2 Agam. Supporting informants in this study were students and school principals. Based on the findings of the research conducted by the researchers, it shows that the implementation of tahfidz Quran extracurricular activities at MAN 2 Agam is carried out in 3 activities, namely initial, core and closing activities. Initial activities include greeting, reading prayers, taking student absences. provide motivation, convey learning objectives and steps of the learning process. The core activities include providing tahfizh material according to the abilities of the students and the time allotted. Closing activities include conveying learning conclusions to students, and conducting evaluations. The supporting factors are the application and policies of the principal towards the Tahfiz Qur'an extracurricular, the facilities and infrastructure and the inhibiting factors namely time constraints, the lack of seriousness of students in participating in the extracurricular tahfiz Qur'an.